Dynamic Modeling and Control of a Flexible Link Manipulators with Translational and Rotational Joints - Bien, Duong (VNU Journal of Science: Mathematics - Physics; Vol 34 No 1DO - 10.25073/2588-1124/vnumap.4240, 2018)
Flexible link manipulators are widely used in many areas such the space technology, medical, defense and automation industries. They are more realistic than their rigid counterparts in many practical conditions. Most of the investigations have been confined to manipulators with only rotational joint. Combining such systems with translational joints enables these manipulators more flexibility and more applications. In this paper, a nonlinear dynamic modeling and control of flexible link manipulator with rigid translational and rotational joints is presented. This model TR (Translational-Rotational) is developed based on single flexible link manipulator with only rotational joint. Finite element method and Lagrange approach are used to model and build equations of the motion. PID controller is designed with parameters (Kp, Ki, Kd) which are optimized by using Particle Swarm Optimization algorithm (PSO). Errors of joints variables and elastic displacements at the end-effector point are reduced to warrant initial request. The results of this study play an important role in modeling generalized planar flexible two-link robot and in selecting the suitable structure robot with the same request.